2005
DOI: 10.1192/bjp.186.5.394
|View full text |Cite
|
Sign up to set email alerts
|

The Danish National Schizophrenia Project: prospective, comparative longitudinal treatment study of first-episode psychosis

Abstract: Integrated treatment and supportive psychodynamic psychotherapy in addition to treatment as usual may improve outcome after 1 year of treatment for people with first-episode psychosis, compared with treatment as usual alone.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
39
0
3

Year Published

2006
2006
2020
2020

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 66 publications
(42 citation statements)
references
References 16 publications
0
39
0
3
Order By: Relevance
“…Studies on the course of schizophrenia have found that substance abusers not only have an higher frequency of relapse (Linszen et al, 1994;Rosenbaum et al, 2005), higher health care cost (Bartels et al, 1993) and a worse social adaptation (Caton et al, 2007), but also present several clinical conditions such as more severe hostile attitudes , more frequent thought disorders (Soyka et al, 2001) and fewer severe negative symptoms (Hambrecht and Häfner, 1996;Bühler et al, 2002;Compton et al, 2004;Bersani et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Studies on the course of schizophrenia have found that substance abusers not only have an higher frequency of relapse (Linszen et al, 1994;Rosenbaum et al, 2005), higher health care cost (Bartels et al, 1993) and a worse social adaptation (Caton et al, 2007), but also present several clinical conditions such as more severe hostile attitudes , more frequent thought disorders (Soyka et al, 2001) and fewer severe negative symptoms (Hambrecht and Häfner, 1996;Bühler et al, 2002;Compton et al, 2004;Bersani et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Several studies describe the valuable role of this intervention within integrated treatment for psychosis (Rosenbaum 2005(Rosenbaum , 2013Seikkula 2006). Nevertheless, in the past two decades, partly owing to lack of evidence of efficacy, psychoanalytic approaches to psychosis treatment in the UK have fallen out of favour with general psychiatry.…”
Section: Current Usementioning
confidence: 99%
“…The sample is a sub-sample from the DNS-multi centre study, a prospective, comparative longitudinal treatment study of firstepisode psychosis including 562 patients from a total of 14 centres representing both rural and urban areas. The sample is described in more detail by Rosenbaum et al (2005). The self-image of participants was measured in seven of the 14 centres.…”
Section: Participantsmentioning
confidence: 99%